Werther's Goethe and the Game of Literary Creativity - Vincent, Deirdre (Book collections on Project MUSE., 1992)
Goethe's Die Leiden des jungen Werther has received a great deal of attention from the scholarly community over the years. But until now it has never been thoroughly explored or evaluated. Deirdre Vincent examines the two versions of Werther in the context of Goethe's personal life in the intervening years. Goethe wrote and published the original version of this novel to great acclaim throughout Europe in 1774, drawing on the experience of a traumatic love affair he had had in Wetzlar in 1772. When the revised work was published some thirteen years later, the public saw the second version as little more than a reissuing of the original, and scholars over the past two centuries have persisted in this view. Vincent analyses Goethe's mode of writing and the role that literary creativity played for him during the first ten years or so in Weimar. She reveals how greatly the second version differs from the first, and challenges conventional explanations for the changes. Vincent sheds new light on Werther and on some of Goethe's other important works written between 1776 and 1789.